Case ReportCoexistence of lichen planus and ulcerative colitis – a case report - Ślebioda, Zuzanna; Szponar, Elżbieta (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2011)
The coincidence of a few diseases related to auto-aggression in one patient has already been reported in the current Polish and foreign medical literature. A case of a 36-year-old male who suffered from two diseases of autoimmune origin – lichen planus and ulcerative colitis – is presented in this paper. The diagnosis of oral reticular lichen planus was made based on typical clinical findings in the oral cavity and confirmed in histopathological examination of the buccal mucosa specimen. To exclude candidiasis, culture on Candida-selective medium was also performed.